The Kalmar Union and the Polish-Lithuanian Union (part 2) – the legal foundations and the later history of the two state unions - Bąk, Hubert; Gaca, Andrzej (Studia Iuridica Toruniensia, 2023)
The authors’ objective is to indicate the need to continue comparative studies of the Polish-Lithuanian union with the Kalmar union. The first part of the article focuses on the genesis and origins of these state unions. The subject of comparison comprises, inter alia, the time and causes of their creation and the circumstances of their conclusion, as well as the stages of social, political, legal, and institutional development of the states forming them (part 1). In the second part, the authors concentrate on a brief presentation of the further history and subsequent transformation of the nature of these unions and an analysis of the Articles of Associa- tion (part 2). These issues are presented principally from a comparative perspective, taking into account the mutual differences and similarities of the two unions. In the authors’ view, the fundamental research problems that could be- come the subject of comparative studies include, among others, an attempt to compare and evaluate the disputes that have arisen among historians over the interpretation of the Latin term applicare on the one hand, and the validity and significance of the deed of union concluded in Kalmar and its relationship to the homagial deed on the other. The subsequent fate of the two unions, with particular reference to the rivalry between the union states and the effects this rivalry has produced, may also be the subject of comparative research. In the authors’ opinion, it would also be advisable to continue the research commenced by Zenon Hubert Nowak into the cooperation between the two unions, with the proviso that the research should focus particularly on the period omitted by Nowak, i.e. up to 1411 and after 1425. It then seems expedient to provide answers as to why the two state unions failed to realise their military and economic potential and to undertake wider cooperation, as well as to present the impact of the two unions on the contemporary relations of the states that comprised them.